EFFECT OF FRUIT THINNING INTENSITY ON FIVE VARIETIES OF LYCHEE - Cavallari Peres, Ludmilla de Lima; Geraldo Martins, Antonio Baldo [UNESP]; Barreto, Livia Felicio [UNESP]; Pimentel, Uliana Vieira (Univ Fed Rural Semi-arido-ufersa, 2017)
Fruit thinning is the removal of fruitlets in heavy fruit set situations and aims to increase salable fruit sizes, avoid branch breakdown, reduce harvesting costs, and promote a balance between the vegetative and reproductive growth of plants. Furthermore, this procedure may improve coloring, increase soluble solids, and maintain plant vigor. This study aimed to evaluate the effects of fruit thinning in five varieties of lychee (Bengal, American, Mauritius, Sweet Cliff, and WB4), in the conditions of Jaboticabal -Sao Paulo state (Brazil). The experimental design was a completely randomized design (CRD) with five treatments and seven replications of three plants each. Treatments consisted of fruit thinning intensities characterized by the number of fruit left on terminal branch panicles, being T1: 3 fruits/branch; T2: 6 fruits /branch; T3: 9 fruit/ branch; T4: 12 fruits/branch; T5: no thinning (control plot). Evaluations were made through a colorimetric assay on ripe fruits, besides a physical and chemical analysis for each variety. The treatments affected the response of varieties on each studied variable. The variety, Mauritius. showed interesting physical and chemical characteristics for the consumer market.
Keywords: Chemical analysis; Colorimetry; Fruit; Litchi chinensis